GAMIFIKASI DAN KORELASINYA DENGAN MINAT MENGUNJUNGI ULANG PADA MARKETPLACE “X” - Bimo Wicaksono; Fransiska Anita Subari (Jurnal Administrasi Bisnis, 2021)
How people enjoy games, especially online games, is seen as an opportunity to attract visitors, in this case marketplace visitors. In contrast to offline stores where visitor traffic can be increased through various gimmicks, events, and so on. One of the efforts that the marketplace can make to increase visitor traffic is through the provision of online game services. The fun, addictive nature of the game has made market participants interested in incorporating game elements into a business that is not related to games. This became known as gamification. Marketplace X is one of the marketplaces that provides gamification game services. With repeated visitors accessing the gamification, it is hoped that the marketing efforts of Marketplace X will be exposed to users. This study intends to determine whether there is a relationship between gamification and the interest in revisiting the marketplace. This study uses quantitative research methods supported by SPSS data processing tools to test hypotheses. The data collection technique uses a purposive sampling technique in which the respondents are those who have played gamification in marketplace X and are domiciled in the city of Bandung. The results show that the gamification offered by Marketplace X is considered good by respondents and respondents have a high intention to revisit the marketplace in the future. In addition, there is a fairly strong correlation between gamification and re-visit intention. Therefore, Marketplace X needs to manage its gamification well to attract repeat visits, which is one way to marketing its products. Keywords: gamification, online games, marketplace, re-visit intention